Promoting and supporting breastfeeding in a protracted emergency setting—Caregivers' and health workers' perceptions from North-East Nigeria - Amat Camacho, Nieves; Chara, Abdullahi; Briskin, Emily; Pellecchia, Umberto; Kyi, Htet Aung; de Rubeis, Maria Livia; Hussain, Faisal; Ahmed, Tasneem; Ogundipe, Oluwakemi F.; Burzio, Chiara; Kamis, Uba; Bukar, Lawan M.; et al. (Frontiers in Public Health, 2023)
Background: Breastfeeding (BF) should be protected, promoted, and supported for all infants in humanitarian settings. The re-establishment of exclusive BF is also a central part of the management of acutely malnourished infants under six months (<6m). Médecins Sans Frontières (MSF) runs a nutrition project in Maiduguri, a protracted emergency setting in North-East Nigeria. This study aimed to explore caregivers (CGs) and health workers (HWs) perceptions of BF practice, promotion, and support among CGs with infants <6m in this setting. Methods: We conducted a qualitative study using in-depth interviews and focus group discussions combined with non-participant observations. Participants included CGs of young infants enrolled in MSF nutritional programs or who attended health promotion activities in a displacement camp. MSF HWs were involved at different levels in BF promotion and support. Data was collected involving a local translator and analyzed using reflexive thematic analysis directly from audio-recordings. Results: Participants described how feeding practices are shaped by family, community and traditional beliefs and practices. The perception of breastmilk insufficiency was common and led to early supplementary feeding with inexpensive but unsuitable products. Participants often linked insufficient breastmilk production with poor maternal nutrition and stress, in a context shaped by conflict and food insecurity. BF promotion was generally well received but could be improved if tailored to address specific barriers to exclusive BF. Interviewed CGs positively valued BF support received as part of the comprehensive treatment for infant malnutrition. One of the main challenges identified was the length of stay at the facility. Some participants perceived that improvements in BF were at risk of being lost after discharge if CGs lacked an enabling environment for BF. Conclusion: This study corroborates the strong influence of household and contextual factors on the practice, promotion, and support of BF. Despite identified challenges, the provision of BF support contributed to improvements in BF practice and was positively perceived by CGs in the studied setting. Greater attention should be directed towards providing support and follow-up for infants <6m and their CGs in the community.